2023
DOI: 10.3390/cells12141826
|View full text |Cite
|
Sign up to set email alerts
|

Oral Delivery of mRNA Vaccine by Plant-Derived Extracellular Vesicle Carriers

Abstract: mRNA-based vaccines were effective in contrasting SARS-CoV-2 infection. However, they presented several limitations of storage and supply chain, and their parenteral administration elicited a limited mucosal IgA immune response. Extracellular vesicles (EVs) have been recognized as a mechanism of cell-to-cell communication well-preserved in all life kingdoms, including plants. Their membrane confers protection from enzyme degradation to encapsulated nucleic acids favoring their transfer between cells. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Using a proprietary technique [ 115 ], we engineered EVs purified from orange juice (Citrus sinensis) (oEVs) with SARS-CoV-2 mRNA coding for Spike S1 subunit (S), Full Spike (FS), and nucleocapsid (N) proteins using cation-based interaction combined with controlled osmotic shock ( Figure 2 ) [ 110 ].…”
Section: Edible Plant-derived Evs As a Platform For Mucosal Vaccine D...mentioning
confidence: 99%
See 3 more Smart Citations
“…Using a proprietary technique [ 115 ], we engineered EVs purified from orange juice (Citrus sinensis) (oEVs) with SARS-CoV-2 mRNA coding for Spike S1 subunit (S), Full Spike (FS), and nucleocapsid (N) proteins using cation-based interaction combined with controlled osmotic shock ( Figure 2 ) [ 110 ].…”
Section: Edible Plant-derived Evs As a Platform For Mucosal Vaccine D...mentioning
confidence: 99%
“…Protection was due to encapsulation into oEVs, since Triton X-100 permeabilization of oEV lipid membrane abrogated the resistance to RNase. In vitro experiments demonstrated that the oEV-mediated delivery of viral mRNAs to macrophages was followed by translation into N, S1, and FS proteins and lymphocyte activation [ 110 ]. Moreover, oEV incorporation of mRNA conferred resistance at room temperature up to one year after lyophilization [ 110 ].…”
Section: Edible Plant-derived Evs As a Platform For Mucosal Vaccine D...mentioning
confidence: 99%
See 2 more Smart Citations
“…Plant-derived EVs or PELNVs are alternatives to human-cell-derived EVs for mRNA vaccine delivery. PELNVs are promising for delivering gene-based vaccines since their production is frugal and with a higher yield, they do not cause toxicity, they prevent damage to nucleic acid cargoes from enzymes or stress, and they are modifiable [ 80 , 164 166 ]. PELNVs isolated from plants are resistant to the gastrointestinal tract, have stability, and are without immunogenicity [ 167 ].…”
Section: Introductionmentioning
confidence: 99%